Breaking the Silence : South African Representations of HIV/AIDS - ELLEN GRÜNKEMEIER (James Currey, 2013)
In her photographic series ‘From the Inside’ (2000-2002), the artist Sue Williamson addresses the South African epidemic by engaging with people living with HIV/AIDS who are willing to disclose their status and to pose for portrait shots. She has statements they make about the virus and its effects painted on walls in public places around Cape Town and Johannesburg, which she then also documents as photographs. These are then printed side by side with the portraits. John Masuku, quoted above, is one such subject of the series.1 Both Masuku’s statement and his participation in the art project demonstrate his openness about HIV/AIDS and his commitment to public discussion. Sue Williamson and John Masuku thus unite their productive and artistic